MEMBANGUN LEARNING COMMUNITY DAN PENINGKATKAN KOMPETENSI MELALUI LESSON STUDY - Sudirtha, I Gede (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Development of a sustainable human resources is imperative to be able to overcome all the problems facing every nation in the midst of the current global competition. The passage of the Asian Economic Community (AEC), besides a new hope for the Asian countries, also have consequences on various aspects of national life. Currently produced human resource education in Indonesia has not been able to properly prepared for these conditions. College graduates still have not been able to compete well with foreign labor. Foreign workers far better prepared to compete in terms of capabilities (skills) and the mastery of the English language compared to Indonesian workers. Kompas.com, 27 April 2015 mentions college graduates Indonesia is experiencing a dilemma, because higher education diploma degree they achieved no longer so easy to get a job guarantee. The difficulty of obtaining employment of university graduates seen from Indonesia educated unemployment rate is increasing every year. Central Statistics Agency (BPS) in August 2014, in Indonesia there are 9.5 percent (688 660 people) of the total unemployed who are alumni of the college. To prepare human resources through education, offered a solution to increase the competence of human resources (graduates of educational institutions) through the establishment of community learning (learning community) and the ongoing collaboration with various parties through the lesson Study.